Larval biotopes of mosquitoes (Diptera: Culicidae) on the Berezinsky Biosphere Reserve (Belarus) - D. S. Suslo (Российский паразитологический журнал, 2022)
The purpose of the research is to study of larval biotopes of the family Culicidae Meigen, 1818 on the territory of the Berezinsky Biosphere Reserve.Materials and methods. Mosquito larvae collected on the Berezinsky Biosphere Reserve in 2016–2020. A total of 7772 mosquito larvae were collected in the course of 1467 counts. Mosquito larvae were collected in four types of natural reservoirs: permanent open (I); permanent shaded (II); temporary open (III) and temporary shaded (IV). The larvae were collected by dip net. The specimens were identifed using standard keys; in certain cases, the taxonomic collection of the Zoological Institute of the Russian Academy of Sciences (St. Petersburg) was used.Results and discussion.We found larvae of 22 mosquito species on the Berezinsky Biosphere Reserve. The genus Aedes Meigen, 1818 is the most abundant – 16 species (72,7%). The genus Anopheles Meigen, 1818 is represented by 2 species (9,2%), the genus Culiseta Felt, 1904 – 3 species (13,6%) and the genus Culex Linnaeus, 1758 – 1 species (4,5%). The largest number of species (18) is recorded in permanent and temporary open-type reservoirs, 17 – in temporary shaded reservoirs and the smallest number – 6 in permanent shaded reservoirs. Three species, Aedes vexans (Meigen, 1830), Ae. cantans (Meigen, 1818), and Ae. sticticus (Meigen, 1838) were found at all types of water bodies. The main larval breeding habitats are reservoirs of temporary origin with varying degrees of shading (88,0%). There are the highest abundance and mean average density of larvae. Thus, in temporary open water bodies, the abundance is 52,4% (with an average density of 197,0±45,7 sp./m2), and in temporary shaded water bodies, the abundance is 35,5% (with an average density of 287,2±162,1 sp./m2). For permanent reservoirs with varying degrees of shading, a low abundance and an average density of larvae are noted. Thus, in permanent open water bodies, the abundance is 9,6% (with an average density of 27,0±7,7 sp./m2), and in permanent shaded water bodies, the abundance is 2,5% (with an average density of 19,4±6,0 sp./m2). In permanent open water bodies, the greatest species diversity is noted, which is confrmed by the values of the indices (Нʹ = 3,06; D Mg = 2,57 and DSm = 0,16).